Economic Value of Energy and Petrochemical Companies and Multiple Directorships: Evidence from Saudi Arabia (2022)
The existence of multiple directorships is the case when a board member is serving on two or more boards or a number of other external appointments. This study aims to examine the impact of multiple directorships on a firm’s economic values among Saudi listed companies using the busyness hypothesis. As for the methodology, this study collected secondary data from the annual reports of the listed companies that include corporate governance and firm-specific characteristics. In addition, this study reviewed the extant research related to the multiple directorships and firms’ economic values. Using a sample of 140 Energy and Petrochemical companies for the period 2012-2019, the Ordinary-Least Square (OLS) results show that busy directors negatively influence the firm’s economic value, measured as ROA and ROE. The findings of this study have theoretical implications in a manner that gives support to the busyness hypothesis in the Saudi context, which is considered a different setting from other studies conducted in other developed and developing countries in terms of politics, economic factors, and culture. This study adds additional empirical evidence in the unique setting of Saudi Arabia. In addition, the findings of this study could have practical implications to policymakers, shareholders, management, auditors, and other stakeholders in gaining a deeper understanding of how multiple directorships negatively influence the firm’s economic value.